2021
DOI: 10.1016/s2213-2600(20)30471-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials in critical care: can a Bayesian approach enhance clinical and scientific decision making?

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 57 publications
(72 reference statements)
0
53
0
Order By: Relevance
“…52 The analytical strategy-ie, the use of a Bayesian design, as in REMAP-CAP, 26 versus frequentist approaches-might be another source of observed discrepancies. 53 For example, the use of adaptive platforms within a Bayesian framework could maximise the finding and interpretation of a beneficial effect. Furthermore, the choice of priors and stopping rules affect the decision to stop enrolment (or not) and will thus change the final estimated effect of a given trial.…”
Section: Outcome Selection and Analytical Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…52 The analytical strategy-ie, the use of a Bayesian design, as in REMAP-CAP, 26 versus frequentist approaches-might be another source of observed discrepancies. 53 For example, the use of adaptive platforms within a Bayesian framework could maximise the finding and interpretation of a beneficial effect. Furthermore, the choice of priors and stopping rules affect the decision to stop enrolment (or not) and will thus change the final estimated effect of a given trial.…”
Section: Outcome Selection and Analytical Strategymentioning
confidence: 99%
“…Importantly, it has been shown that the conclusions from frequentist and Bayesian analysis of the same evidence are not always consistent. 53…”
Section: Outcome Selection and Analytical Strategymentioning
confidence: 99%
“…A Bayesian reanalysis can be a helpful tool to augment the interpretation of critical care trials ( 8 , 17 , 18 , 33 37 ). In this review, we have highlighted potential challenges with the interpretation of results from a trial conducted using frequentist methods.…”
Section: Discussionmentioning
confidence: 99%
“…The primary controversy stems from confusion and frustration regarding the meaning (and thus the interpretation) of P values and null hypothesis testing, which are statistical concepts employed to design and analyze trials in an approach to statistics known as frequentism ( 1 ). One consequence of this debate regarding RCTs is a surging interest in Bayesian statistical thinking, which can be used to design, analyze, and interpret new clinical trials or to reanalyze trials reported using frequentist methods in an attempt to contextualize the results ( 2 8 ).…”
mentioning
confidence: 99%
“…These designs may be more efficient than traditional trial designs for identifying patients who benefit in settings in which HTE exists within the study population. Frequentist or Bayesian statistical approaches may be used in these designs depending on the complexity of potential modifications ( 35 , 36 ). The additional interim analyses and modifications potentially increase the risk of false positive results.…”
Section: Recommendationsmentioning
confidence: 99%